Peran Orangtua Dan Guru Pendidikan Agama Kristen Dalam Pembentukan Karakter Rohani Siswa Di SMP Negeri 2 Taman Sidoarjo Jawa Timur - Adianto Simanjutak (Jurnal Teologi dan Pelayanan Kerusso, 2022)
The study aims to describe the role of Christian education parents and teachers in the formation of children's spiritual characters. The focus of this research is how Christian education parent and teacher roles are in the formation of child's spiritual character. Research was conducted at Junior high school Negeri 2 Taman Kabupaten Sidoarjo and as a source of data for children's parents, teacher Christian education and a Christian child. Data collection techniques consist of literature reviews, interviews, and documentation. The instruments in this research are interview guidelines, and are denomented. The data analysis technique used in this study is a qualitative data analysis, following the concepts given Miles and Huberman and Spradley. From the results of the analysis of data obtained the conclusion of the parent role in the formation of children's spiritual character in the school Junior high school Negeri 2 Taman Kabupaten Sidoarjo, not entirely fulfilled. While the role of teachers Christian education Junior high school Negeri 2 Taman Kabupaten Sidoarjo, has been done with the maximum, namely as educators, counselors, advisers, motivators, evangelists, communicators, and socialization agents and roles in accordance with the demands of the curriculum K13. Abstrak Indonesia Penelitian ini bertujuan untuk mendeskripsikan peran orang tua dan guru PAK dalam pembentukan karakter spiritual Siswa. Fokus penelitian ini adalah bagaimana peran orang tua dan guru PAK dalam pembentukan karakter spiritual Siswa. Penelitian dilakukan di SMP Negeri 2 Taman Kabupaten Sidoarjo dan sebagai sumber data bagi orang tua Siswa, Guru PAK, dan Siswa Kristen. Teknik pengumpulan data terdiri dari studi pustaka, wawancara, dan dokumentasi. Instrumen dalam penelitian ini adalah pedoman wawancara, dan dekumentasi. Teknik analisis data yang digunakan dalam penelitian ini adalah analisis data kualitatif, mengikuti konsep yang diberikan Miles dan Huberman dan Spradley. Dari hasil analisis data diperoleh kesimpulan peran orang tua dalam pembentukan karakter spiritual Siswa di sekolah SMP Negeri 2 Taman Kabupaten Sidoarjo , belum sepenuhnya terpenuhi. Sedangkan peran guru PAK SMP Negeri 2 Taman Sidoarjo , telah dilakukan dengan maksimal yaitu sebagai pendidik, konselor, pembimbing, motivator, penginjil, komunikator, dan agen sosialisasi dan peran sesuai dengan tuntutan kurikulum K13.